Witnesses to cultural genocide : - American Transylvanian Federation; Committee for Human Rights in Rumania (American Transylvania Federation : Committee for Human Rights in Rumania, 1979)
Introduction / by George Schöpflin -- Modern genocide and its remedy / by Ferenc Kunszabó -- Methods of rumanianization employed in Transylvania / by Anonymous Napocensis -- Memorandum / by György Lázár -- Memorandum (excerpts) / by Lajos Takács -- Three letters to high-ranking Rumanian Communist Party officials / by Károly Király -- Letter to Ferdinand Nagy / by Zoltán Zsuffa -- Between millstones: a letter to the Rumanian intellectuals from sixty-two Hungarian intellectuals living in Rumania.